Diversity and species composition of butterflies (Lepidoptera: Papilionoidea) in Taka Melor Amenity Forest, Labis Forest Reserve, Segamat, Johor, Malaysia - Aqilah Awg Abdul Rahman; Maryati Mohamed; Mohd Syahrir Azrin Salleh (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
This study was conducted to obtain a preliminary checklist of butterflies in Taka Melor Amenity Forest, Labis Forest Reserve, Johor. Butterflies were sampled between February 2018 to September 2018 using aerial net and baited trap. A total of 88 individual butterflies representing 61 species and 43 genera was recorded. Sampling were done on February, July and September 2018 using aerial nets and baited traps. Result shows that Nymphalidae is the most dominant family with 41 individuals and 31 species recorded. All six families of the butterfly were recorded, Papilionidae, Pieridae, Nymphalidae, Riodinidae, Lycaenidae and Hesperiidae. According to the rank abundance curve, the most dominant species within the group is Pantoporia sandaka (Nymphalidae) with five individuals recorded. This is followed by Iambrix salsala (Hesperiidae), Castalius rosimon (Lycaenidae), Ypthima horsfieldi (Nymphalidae) and Appias lyncida (Pieridae) with 4 individuals each. The Shannon Diversity Index for this site is 3.95 with its respective evenness value of 0.9609. Overall the diversity butterflies in Taka Melor is relatively high. This preliminary checklist will provide a baseline data of butterfly species in Taka Melor which may assist conservation management in the future.